The Influence of Electronic Human Resource Management, Strategic Leadership, and Work Motivation on Organizational Performance in Indonesian Army Hospitals: The Mediating Role of Organizational Culture - Ade Permana; Willy Arafah; Sarfilianty Anggiani (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the influence of Electronic Human Resource Management (E-HRM), Strategic Leadership, and Work Motivation on the Organizational Performance of Indonesian Army hospitals, with Organizational Culture as a mediating variable. Implementing this research in the context of military hospitals is expected to enhance the performance of Indonesian Army hospitals. This study employs a quantitative approach with a non-probability sampling method, specifically purposive sampling. The analyzed unit consists of middle-to-upper-level leaders in Indonesian Army hospitals. Data were collected through a questionnaire using a Likert scale of 1–5, distributed to 278 respondents. Structural Equation Modeling (SEM) was utilized to analyze data and examine the relationships between variables, including the mediating role of Organizational Culture. The results indicate that E-HRM does not directly influence Organizational Performance but has a positive effect through Organizational Culture as a mediator. Strategic Leadership significantly and directly impacts Organizational Performance, while Work Motivation does not have a direct influence but positively affects Organizational Performance through Organizational Culture. Additionally, Organizational Culture fully mediates the positive effects of E-HRM and Work Motivation on Organizational Performance and partially mediates the relationship between Strategic Leadership and Organizational Performance. This study contributes to theory and management practices by developing a model integrating E-HRM, Strategic Leadership, and Work Motivation within the Indonesian Army hospital context. It provides insights for optimizing leadership strategies, strengthening Organizational Culture, enhancing Work Motivation, and improving the effectiveness of E-HRM implementation to achieve better Organizational Performance.